Matematika Musik dan Analisis Pola Harmoni sebagai Pendekatan Interdisipliner untuk Menjelaskan Hubungan Sains dan Seni dalam Kreativitas Manusia - Eka Satria Wibawa; Dedy Arisjulyanto (Journal of New Trends in Sciences, 2023)
This study investigates the intrinsic relationship between mathematics and classical music by analyzing harmonic patterns in compositions of renowned composers such as Bach, Mozart, and and Beethoven. The research employs an analytical quantitative approach, using statistical tools to map and identify numerical ratios within musical intervals and the relationships between chords. Data were collected from selected musical works to examine interval structures and harmonic progression patterns. Findings reveal that classical music exhibits consistent mathematical patterns, including the octave (2:1), perfect fifth (3:2), and other proportional relationships that form the basis of chord construction and harmonic coherence. These patterns demonstrate that mathematical principles are inherently embedded in musical compositions, allowing for an objective analysis of music structure without diminishing its aesthetic and emotional value. Furthermore, the study highlights the value of an interdisciplinary perspective, combining quantitative analysis with traditional music aesthetics, which provides new insights into understanding compositional techniques and creativity. The results also suggest that recognizing mathematical structures in music can contribute to a deeper understanding of music theory and education, enhancing how students and scholars approach musical analysis. Overall, this research emphasizes that integrating mathematical and artistic perspectives not only supports the scientific study of music but also encourages a holistic appreciation of the creative process, bridging the gap between art and science while offering practical implications for music pedagogy, theory, and performance studies.